WIDEBAND TRANSFORMER FOR MATCHING OF LOW-IMPEDANCE LOADS IN VERY HIGH FREQUENCY RANGE - N. M. Naumovich; A. P. Joubko; M. V. Davydov; O. S. Maltsev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The article presents the results of preliminary research in the wideband transformer development for matching low-ohms loads in the very high frequency band with the use of a coupled transmission lines. The transmission line was produced with the using of a polyimide in the form of flexible printed circuit board. This way may be useful for wideband matching different cascades with custom values of input and output impedance in the wide band of frequencies and powers with use of a defining impedance capability with a load character in mind. On the first stage, the computer simulation of transformer with a transformer ratio 4:1 in the band (40–240 MHz) was completed for limiting values of input and output resistances – 50 and 12,5 Ohms respectively. Results of simulation give us the data about constructive parameters of the transmission line. The measurement technique for insertion loss was worked out. The reason of that is an impossibility of appliance standard methods with using a network vector analyzer. The prototyping was done and values of the standing wave ratio and inserting losses were obtained for different levels of the input power. According to received data, it can be affirmed, that the manufactured transformer provides the standing wave ratio better (lower) that two. Inserting losses vary from 0,02 to 1,54 dB depending from a input power level (1– 1000 mW). The obtained results afford ground for working continuation in this field – a development of wideband transformers for matching of low-ohms loads.